2017
DOI: 10.1002/hyp.11273
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Beerkan infiltration tests with rainfall simulation experiments for hydraulic characterization of a sandy‐loam soil

Abstract: Saturated soil hydraulic conductivity, Ks, data collected by ponding infiltrometer methods and usual experimental procedures could be unusable for interpreting field hydrological processes and particularly rainfall infiltration. The Ks values determined by an infiltrometer experiment carried out by applying water at a relatively large distance from the soil surface could however be more appropriate to explain surface runoff generation phenomena during intense rainfall events. In this study, a link between rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…All average K fs values were lower than the expected saturated conductivity on the basis of the soil textural characteristics alone, e.g., K s = 4.5 mm·h −1 for a silt loam soil according to Carsel and Parrish [68]. This suggested that soil macroporosity in the control and burnt site did not influence the results [28]. All differences between the average K fs values of different sites and sampling campaigns were not statistically significant according to the Tukey honestly significant difference test (p < 0.05).…”
Section: Performance Of the Cumulative Linearization (Cl) Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…All average K fs values were lower than the expected saturated conductivity on the basis of the soil textural characteristics alone, e.g., K s = 4.5 mm·h −1 for a silt loam soil according to Carsel and Parrish [68]. This suggested that soil macroporosity in the control and burnt site did not influence the results [28]. All differences between the average K fs values of different sites and sampling campaigns were not statistically significant according to the Tukey honestly significant difference test (p < 0.05).…”
Section: Performance Of the Cumulative Linearization (Cl) Methodsmentioning
confidence: 84%
“…The cores were used to determine the soil bulk density, ρ b (g·cm −3 ), and the initial volumetric soil water content, θ i (m 3 ·m −3 ). According to other investigations, the saturated soil water content, θ s (m 3 ·m −3 ), was approximated by total soil porosity, determined from bulk density ρ b (e.g., [28,37,[43][44][45][46][47][48]). Soil organic matter was determined by the Walkley-Black [49] method.…”
Section: Soil Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to check whether soils were entirely saturated at the beginning of our experiment, the calculated soil porosity of 0.43 cm 3 /cm 3 was assumed to coincide with saturated soil water content ε (θs, ε = ε), as suggested by many authors (e.g., Di Prima, ; Minasny et al, ; Prima et al, ). This approach assumes a low to medium spatial variability for both θs and bulk density (Di Prima, ).…”
Section: Methodsmentioning
confidence: 99%
“…The soil porosity, ε (cm 3 /cm 3 ), was calculated from the bulk density data, assuming a soil particle density of 2.65 g/cm 3 (Minasny, McBratney, & Bristow, 1999;Prima et al, 2017).…”
Section: Introductionmentioning
confidence: 99%